Lifetime Induced Abortions and Live Births: A 40-Year Historical Cohort Study - Lidegaard, Øjvind; Zernichow Borberg, Hjarn V; Rasmussen, Steen C; Mikkelsen, Anders P (Journal of obstetrics and gynaecology Canada : JOGC = Journal d'obstetrique et gynecologie du Canada : JOGC, 2024)
Little is known about whether induced abortions are associated with the final lifetime number of live births (life births). The objective of this study was to examine the association between the number of life births with the number of abortions a female has had in her lifetime. In a national cohort design, we followed all Danish females from ages 15 to 44 years through the period 1977-2017 for induced abortions and live births. For each lifetime number of induced abortions, the average number of life births was assessed, and rates with 95% CI were calculated. The study included 409 497 females who completed 222 482 induced abortions and 831 742 live births. Of 265 573 (64.9%) females who did not have any induced abortion, the average number of life births was 2.09 (95% CI 2.08-2.10). For females with 1 (23.4%), 2 (7.4%), 3 (2.6%), 4 (1.0%), and ≥5 (0.7%) induced abortions during their reproductive lifespan, the average number of life births was 1.88 (1.87-1.89), 1.99 (1.98-2.00), 2.09 (2.06-2.11), 2.13 (2.09-2.15), and 2.25 (2.21-2.29), respectively. The increase in number of life births in females with 1 to females with 5+ induced abortions was 4.7% for each additional induced abortion. We found the number of induced abortions during a woman's reproductive lifespan to be positively correlated to the number of live births. This association is likely explained by a high fecundity in females with multiple pregnancies including induced abortions and suggests that even several induced abortions do not compromise a woman's general reproductive end points.